2015
DOI: 10.1016/j.urology.2015.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Partial and Radical Nephrectomy for Unilateral Synchronous Multifocal Renal Cortical Tumors

Abstract: Objective To evaluate clinicopathologic characteristics and treatment outcomes of patients undergoing partial (PN) or radical nephrectomy (RN) for unilateral synchronous multifocal renal tumors. Methods We retrospectively reviewed medical records for 128 patients with non-metastatic unilateral synchronous multifocal renal tumors who underwent surgical resection at our institution from 1995 to 2012. Five patients with hereditary renal cell carcinoma were excluded. Differences between patient and tumor charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…Due to the mulitfocality nature of the tumors, it is theoretically possible for residual tumors to still be present after the surgery. However, most studies have shown that NSS did not increase the rate of tumor recurrence, as well as cancer-specific survival [12][13][14]. Our study identified 21 patients with multifocal RCC who had undergone NSS presented with recurrence and 11 who had undergone RN.…”
Section: Discussionmentioning
confidence: 85%
“…Due to the mulitfocality nature of the tumors, it is theoretically possible for residual tumors to still be present after the surgery. However, most studies have shown that NSS did not increase the rate of tumor recurrence, as well as cancer-specific survival [12][13][14]. Our study identified 21 patients with multifocal RCC who had undergone NSS presented with recurrence and 11 who had undergone RN.…”
Section: Discussionmentioning
confidence: 85%
“…With respect to management, Mano et al, in their retrospective analysis, reported a shift in practice over the years for the surgical treatment of unilateral synchronous multifocal RCCs, as 82% of patients previously underwent radical nephrectomy (RN) between 1995 and 2000, compared with 32% who underwent RN between 2001 and 2012. 11 A trend has developed toward more-frequent use of PN approach. Their study, which included 128 patients, revealed a five-year recurrence-free survival of 98% for PN and 85% for RN but a statistically insignificant difference in five-year overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Their study, which included 128 patients, revealed a five-year recurrence-free survival of 98% for PN and 85% for RN but a statistically insignificant difference in five-year overall survival. 11 They attribute this difference in recurrence to the fact that patients who underwent PN had more favourable tumour characteristics. As for overall survival, Siracusano and colleagues showed that multifocality is not an independent risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 15 In addition, when they compared the 2 main surgical options for managing this subset of patients, similar tumor-specific survival was observed for patients treated with nephron-sparing surgery NSS and radical nephrectomy RN in carefully selected patients. 7 , 11 , 12 , 15 , 18 …”
Section: Discussionmentioning
confidence: 99%